KAJIAN MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL 3 (TIGA) JENIS JAGUNG (ZEA MAYS L.) - Fitri Wahyuningsih; Sri Hardiatmi; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2020)
The research about “Study Kind of Animal Manures to Against Growth and Yield of 3 (Three) Types of Corn (Zea Mays L.) " which has been carried out from 4 November 2019 to 17 January 2020 in Sidorejo Hamlet, Sajen Village, Trucuk District, Klaten Regency, Central of Java with a height of place 130 (masl) with regosol soil type. This study aims to determine the growth and yield of three types of corn by treatment three types of manure. In this study using a factorial Randomized Completion Block  Design (RCBD) with method arranged split plot or separate tile layout design consist of 2 factors treatment and each was repeated 3 times to get 12 combinations. Types of Corn (V): V1: Yellow Corn, V2: White Corn, V3: Black Corn. Type of Manure (P), P0: Without Granting Manure, P1: Cow Manure, P2: Goat Manure, P3: Chicken Manure. Data from the results of this study were analyzed by LSD test (Least Significant Difference) at the 5% level, and resulted that: (1) There was no interaction between manure and three types of corn on all observed parameters, namely plant height, number of leaves, stem diameter, cob length, cob diameter, number of fresh cobs per plant, weight of fresh cobs per plant, weight of fresh cobs per the plot, (2) Giving kinds of chicken manure and black corn types (IPB J1) has an influence on the growth of plant height with the highest average value of 116.33 cm and the number of leaves with the highest average value of 8.17 strands. Then the growth of stem diameter by giving kinds of cow manure influences the three types of corn with the highest yield on yellow corn species (Bonanza F1) with the highest average value of 2.13 cm, (3) The provision of goat manure manure gives the best results on the weight of fresh cobs of yellow corn (Bonanza F1) of 343.45 gr / plant and white corn (Kumala F1) 243.54 gr / plant.